Criminal Responsibility Of Influencers Who Promote Online Gambling On Social Media - Muhammad Irfan Amnan; Miftahul Jannah; Moch Andry Wikra Wardhana (COMPENDIUM OF JUDGE MADE LAW, 2025)
This research aims to find out and analyse the Criminal Responsibility of Influencers Who Promote Online Gambling on Social MediaThis research is carried out using the Normative research method, also called doctrinal law research, which is often conceptualised as what is written in laws and regulations or laws are conceptualized as rules or norms that are benchmarks for human behaviour that are considered appropriate.The results of this study show that (1) in terms of online gambling, this mode shows how flexible online gambling activities are carried out. The mode of promoting online gambling has certainly been regulated in Article 27 paragraph (2) jo. Article 45 paragraph (2) of the ITE Law explains that any person who intentionally and without the right to distribute, transmit, and/or make accessible electronic information and/or electronic documents that have the content of gambling as referred to in Section 27 paragraph (2) shall be sentenced to a maximum prison sentence of 10 (ten) years and/or a maximum fine of Rp 10,000,000,000.00 (ten billion rupiah). (2) Legal regulations regarding criminal liability for influencers who promote online gambling are expressly regulated in Law No. 11 of 2008 (UU ITE), Article 27 paragraph 2 of the ITE Law becomes the main legal basis that prohibits all forms of distribution, transmission, or provision of access to electronic information loaded with online gambling.